Laminate including an inorganic nanoparticle-containing surface layer exhibiting a low gloss appearance and an inorganic nanoparticle-containing radiation-curable ink

JP7641707B2Active Publication Date: 2025-03-073M INNOVATIVE PROPERTIES CO
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2019209807
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-11-20
Publication Date
2025-03-07
Estimated Expiration
2039-11-20

AI Technical Summary

Benefits of technology

【0012】 本開示によれば、低光沢な外観を呈する無機ナノ粒子含有表面層を含む積層体及び無機ナノ粒子含有放射線硬化型インクを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641707000006
    Figure 0007641707000006
  • Figure 0007641707000007
    Figure 0007641707000007
  • Figure 0007641707000008
    Figure 0007641707000008
Patent Text Reader

Abstract

To provide a laminate having inorganic nanoparticle-containing surface layer that exhibits a low gloss appearance, and inorganic nanoparticle-containing radiation-curable ink.SOLUTION: A laminate 100, 110 has a substrate 101 and a surface layer 102, 105 containing a cured product of a radiation-curable ink, the radiation-curable ink containing inorganic nanoparticles, a polyether-modified polymer, and at least one selected from the group consisting of a radiation-curable polymerizable oligomer and a radiation-curable polymerizable monomer, and the surface layer having a 60° surface glossiness of 50.0 GU or less. The radiation-curable ink can bring the inorganic nanoparticles contributing to a low gloss appearance close to the surface of the surface layer through irradiation.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to laminates and radiation curable inks that include a surface layer that exhibits a low gloss appearance. [Background technology]

[0002] For example, in display devices such as liquid crystal displays, light diffusing sheets are used to prevent a decrease in visibility of the screen. Also, decorative films that are embossed for the purpose of decorating the interior and exterior of buildings, vehicles, etc. are known.

[0003] Patent Document 1 (Japanese Patent No. 3743624) describes a light diffusing sheet including a light diffusing layer made of a resin film layer having a fine unevenness formed on its surface, the 60° gloss value (JIS Z8741) of the fine unevenness surface varies depending on the direction of incidence, and the maximum value (a) and minimum value (b) of the gloss value satisfy the formula: (ab)>{(a+b) / 2}×0.1.

[0004] Patent Document 2 (JP 2011-255552 A) describes an embossed decorative sheet in which the surface of a decorative sheet is embossed, and a surface protection layer made of a curable resin containing synthetic resin beads is provided on the surface side of the decorative sheet, the embossing has an average amplitude of 15 to 50 micrometers, and the synthetic resin beads have an average particle size of 8 to 20 micrometers.

[0005] Patent Document 3 (JP 2019-072935 A) describes an extensible film having a surface layer containing a binder containing a urethane resin, urethane resin beads having an average particle size of 4 to 20 micrometers, and nanosilica particles, and having a surface gloss of 5 GU or less at 60 degrees.

[0006] In recent years, for example, in optical applications and decorative applications, films and the like that exhibit a low-gloss appearance are in demand. When a low-gloss appearance is realized by a mechanical means such as embossing, maintenance and management of equipment such as an embossing roll is required, and a different embossing roll is required for each required low-gloss appearance, leading to increased costs.

[0007] A technique is also known in which resin beads or the like are blended into the ink to roughen the surface of the printed layer or coating layer, but there are cases in which a good low-gloss appearance cannot be achieved because the resin beads settle in the layer, etc. In recent years, it has become possible to produce a low-gloss layer using an inkjet printer, but resin beads cannot be used due to restrictions on the size of the inkjet head, and it has been difficult to achieve low gloss due to restrictions on viscosity. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 3743624 [Patent Document 2] JP 2011-255552 A [Patent Document 3] JP 2019-072935 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present disclosure provides laminates including inorganic nanoparticle-containing surface layers and inorganic nanoparticle-containing radiation-curable inks that exhibit a low gloss appearance. [Means for solving the problem]

[0010] According to one embodiment of the present disclosure, there is provided a laminate comprising a substrate and a surface layer comprising a cured product of a radiation curable ink, wherein the radiation curable ink comprises inorganic nanoparticles, a polyether modified polymer, and at least one selected from a radiation curable polymerizable oligomer and a radiation curable polymerizable monomer, and the surface layer exhibits a 60 degree surface gloss of 50.0 GU or less.

[0011] According to another embodiment of the present disclosure, there is provided a radiation-curable ink comprising inorganic nanoparticles, a polyether-modified polymer, and at least one selected from a radiation-curable polymerizable oligomer and a radiation-curable polymerizable monomer. Effect of the Invention

[0012] According to the present disclosure, it is possible to provide a laminate including an inorganic nanoparticle-containing surface layer that exhibits a low gloss appearance, and an inorganic nanoparticle-containing radiation-curable ink.

[0013] It should be noted that the above description should not be construed as a disclosure of all embodiments of the present invention and all advantages related to the present invention. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2A is a schematic cross-sectional view of a laminate according to an embodiment of the present disclosure before irradiation, and FIG. 2B is a schematic cross-sectional view of the laminate after irradiation. [Diagram 2] 1(a) is an SEM photograph of the upper surface of the laminate of Comparative Example 1 having a surface layer containing a polyether-modified polymer but no inorganic nanoparticles, and FIG. 1(b) is an SEM photograph of a cross section of the surface layer of the laminate of Comparative Example 1. [Diagram 3] 1A is an SEM photograph of the upper surface of the laminate of Comparative Example 2, which has a surface layer containing inorganic nanoparticles but no polyether-modified polymer, and FIG. 1B is an SEM photograph of a cross section of the surface layer of the laminate of Comparative Example 2. [Figure 4]1(a) is an SEM photograph of the upper surface of the laminate of Example 1 having a surface layer containing inorganic nanoparticles and a polyether-modified polymer, and FIG. 1(b) is an SEM photograph of a cross section of the surface layer of the laminate of Example 1. [Diagram 5] The top left of (a) is an SEM photograph taken at an inclination angle of 10 degrees of the laminate surface of Comparative Example 3, which has a conventional uneven surface layer prepared using an inkjet ink that does not contain a polyether-modified polymer and inorganic nanoparticles; the bottom left is an SEM photograph of the top surface of this uneven surface layer; and the right side is an optical photograph of the laminate surface of Comparative Example 3, which has a conventional uneven surface layer. The top right of (b) is an SEM photograph taken at an inclination angle of 10 degrees of the laminate surface of Example 14, which has a uneven surface layer of one embodiment of the present disclosure prepared using an inkjet ink containing a polyether-modified polymer and inorganic nanoparticles; the bottom right is an SEM photograph of the top surface of this uneven surface layer; and the left side is an optical photograph of the laminate surface of Example 14, which has a surface layer prepared using an ink of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described in more detail below for the purpose of illustrating representative embodiments thereof, but the present invention is not limited to these embodiments.

[0016] In the present disclosure, "nanoparticles" refers to particles on the nanometer order, i.e., particles with a size of less than 1000 nm.

[0017] In the present disclosure, the term "radiation curable" refers to the ability to be cured by radiation such as ultraviolet light, electron beams, or X-rays.

[0018] In the present disclosure, "non-functional" means the ability to not undergo a curing reaction with the compound of formula 1, radiation-curable oligomer or monomer, etc., contained in the ink even when exposed to radiation.

[0019] In this disclosure, "(meth)acrylic" means acrylic or methacrylic, "(meth)acrylate" means acrylate or methacrylate, and "(meth)acryloyl" means acryloyl or methacryloyl.

[0020] In this disclosure, "monofunctional monomer" means a compound that has only one reactive functional group and generally has a weight average molecular weight of less than 1000.

[0021] In the present disclosure, "oligomer" refers to a compound having a plurality of units derived from a monomer, and generally has a weight average molecular weight of at least 500, or at least 1000. For example, a urethane (meth)acrylate oligomer is a compound that contains a plurality of units having a urethane bond and has a (meth)acryloyloxy group.

[0022] In the present disclosure, for example, "on" in "the decorative layer is disposed on the substrate" means that the decorative layer is disposed directly on the upper side of the substrate, or that the decorative layer is disposed indirectly on the upper side of the substrate via another layer.

[0023] In the present disclosure, for example, "under" in "the adhesive layer is disposed under the substrate" means that the adhesive layer is disposed directly under the substrate, or that the adhesive layer is disposed indirectly under the substrate film via another layer.

[0024] In the present disclosure, the term "film" also encompasses an article called a "sheet."

[0025] In this disclosure, the term "approximately" means including variations that occur due to manufacturing errors and the like, and is intended to allow for a variation of about ±20%.

[0026] In the present disclosure, "transparent" refers to an average transmittance in the visible light region (wavelength 400 nm to 700 nm) measured in accordance with JIS K 7375 of 80% or more, and may be desirably 85% or more, or 90% or more.

[0027] In the present disclosure, the term "semi-transparent" refers to an average transmittance in the visible light region (wavelength 400 nm to 700 nm) measured in accordance with JIS K 7375 of less than 80%, and may desirably be 75% or less, or may be 10% or more, or 20% or more, and is intended to not completely conceal the base.

[0028] With reference to the drawings, laminates of the present disclosure are illustrated.

[0029] Fig. 1 is a cross-sectional view of a laminate 100 before radiation exposure and a laminate 110 after radiation exposure according to one embodiment of the present disclosure. The laminate 100 in Fig. 1(a) has a surface layer 102 before radiation exposure on a substrate 101, and the laminate 110 in Fig. 1(b) has a surface layer 105 after radiation exposure on the substrate 101. Both surface layers contain inorganic nanoparticles 103 and a binder resin 104 obtained by curing at least one selected from a radiation-curable polymerizable oligomer and a radiation-curable polymerizable monomer.

[0030] Hereinafter, for the purpose of illustrating representative embodiments of the present disclosure, details of each component will be described with some reference numerals omitted.

[0031] The laminate of the present disclosure comprises a surface layer prepared from a radiation-curable ink containing inorganic nanoparticles, a polyether-modified polymer, and at least one selected from a radiation-curable polymerizable oligomer and a radiation-curable polymerizable monomer.

[0032] In the radiation-curable ink of the present disclosure, the inorganic nanoparticles are not substantially aggregated or coalesced in the ink, and when such an ink is applied to the surface of a substrate, the inorganic nanoparticles can be dispersed approximately uniformly in the surface layer as shown in Figure 1(a). The present inventors unexpectedly found that when a radiation-curable ink containing inorganic nanoparticles and a polyether-modified polymer is used, at least a portion of the inorganic nanoparticles in the surface layer applied to the surface of a substrate can migrate to the vicinity of the surface of the surface layer upon irradiation with radiation as shown in Figure 1(b), thereby exhibiting a low gloss appearance.

[0033] In the radiation-curable ink of the present disclosure, aggregation and coalescence of inorganic nanoparticles are unlikely to occur in the ink, and therefore clogging of the ink ejection nozzle or the wire wound around the coating roll can be reduced or prevented. For example, conventional inks that incorporate coarse particles on the order of micrometers to achieve a low gloss appearance have limitations in printing or coating methods, and inkjet printing methods, for example, cannot be used. However, the radiation-curable ink of the present disclosure can coarse particles by aggregating or concentrating them after application to a substrate, and is therefore not subject to the limitations of printing or coating methods, and is advantageous in terms of productivity, etc.

[0034] The inorganic nanoparticles to be used are not particularly limited, and for example, at least one type of particle selected from silica, alumina, titanium oxide, zinc oxide, zirconium oxide, tin-doped indium oxide, cesium tungstate, and antimony-doped tin oxide can be used. Among them, silica nanoparticles are preferred from the viewpoints of interaction with any compound of formula 1 or non-functional silane coupling agent that may be blended in the ink, expression of low gloss appearance after irradiation, abrasion resistance, and the like. Here, the "inorganic nanoparticles" in the present disclosure do not include inorganic pigments such as carbon black that are used in inkjet inks, for example.

[0035] As the silica nanoparticles, for example, silica sol obtained by using water glass (sodium silicate solution) as a starting material can be used. For example, when using a dispersion liquid in which silica nanoparticles are dispersed in isopropanol or the like, from the viewpoint of the expression of a low gloss appearance after irradiation or from the viewpoint of reducing or preventing defects such as gelation of the ink, it is preferable that the starting material dispersion liquid contains little or no acid components, alkali components, and ion components, particularly ammonia, acetic acid, hydrochloric acid, sodium ions, potassium ions, and calcium ions. Therefore, the contents of acid components, alkali components, and ion components, particularly ammonia, acetic acid, hydrochloric acid, sodium ions, potassium ions, and calcium ions in the ink prepared using such a dispersion liquid or in the surface layer formed by such an ink, based on the total solids weight of the ink or based on the total weight (dry coating weight) of the surface layer, are preferably 500 ppm or less, 300 ppm or less, 100 ppm or less, 10 ppm or less, or 1 ppm or less, and more preferably these components are not contained.

[0036] From the viewpoint of expressing a low gloss appearance after irradiation or reducing or preventing gelation of the ink, the silica nanoparticles in such a dispersion are advantageously unmodified particles whose surfaces have not been modified by a surface treatment agent such as silane, amine, carboxylic acid, sulfonic acid, phosphonic acid, titanate, etc., and isopropanol is advantageously used as the dispersion. As the dispersion containing unmodified silica nanoparticles whose acid component, alkali component, and ion component are within the above ranges, commercially available products can be used, such as IPA-ST, IPA-ST-L, and IPA-ST-ZL manufactured by Nissan Chemical Industries, Ltd.

[0037] The blending amount of the inorganic nanoparticles is not particularly limited, and can be appropriately adjusted based on, for example, the required low gloss appearance, the viscosity of the ink, etc. The blending amount of the inorganic nanoparticles can be, for example, 2% by mass or more, 4% by mass or more, or 6% by mass or more based on the total weight (dry coating amount) of the surface layer or the total weight (solid content) of the ink, and can be 20% by mass or less, 15% by mass or less, or 10% by mass or less.

[0038] Generally, a low gloss appearance is more susceptible to fine irregularities due to inorganic nanoparticles on the surface of the surface layer than to inorganic nanoparticles inside the surface layer. The radiation-curable ink of the present disclosure can migrate inorganic nanoparticles that contribute to a low gloss appearance to the vicinity of the surface of the surface layer by irradiation with radiation, and therefore can reduce the amount of inorganic nanoparticles used compared to inks containing inorganic nanoparticles that do not have such performance. As a result, the radiation-curable ink of the present disclosure can contribute to reducing production costs and improving elongation properties, etc.

[0039] The average particle size of the inorganic nanoparticles is not particularly limited, and may be, for example, 5 nm or more, 7 nm or more, 10 nm or more, 12 nm or more, 20 nm or more, 30 nm or more, or 50 nm or more, and may be 150 nm or less, 120 nm or less, or 100 nm or less, from the viewpoints of expression of a low gloss appearance, ejection properties from an inkjet nozzle, coating properties, etc. The average particle size of the inorganic nanoparticles is the average value of the diameters of 10 or more particles, for example, 10 to 100 particles, measured using a transmission electron microscope (TEM).

[0040] Since the radiation-curable ink of the present disclosure contains a polyether-modified polymer, it is possible to migrate inorganic nanoparticles to the vicinity of the surface of the surface layer by irradiation with radiation.

[0041] The polyether-modified polymer is not particularly limited, and for example, a polyether-modified polymer having a siloxane bond can be used. Examples of such polymers include polyether-modified siloxane polymers, such as "TEGO™ Flow 425" manufactured by Evonik Industries; polyether-modified polydimethylsiloxanes, such as "BYK-UV3510" manufactured by BYK-Chemie Japan; polyether-modified polysiloxanes or polyether-modified polydimethylsiloxanes having one or more (meth)acrylic functional groups, such as "BYK-UV3500", "BYK-UV3505", "BYK-UV3530", "BYK-UV3570", "BYK-UV3575", and "BYK-UV3576" manufactured by BYK-Chemie Japan; and silicone (meth)acrylates, such as "TEGO™ Rad 2250", "TEGO™ Rad 2300", and "TEGO™ Rad 2600" manufactured by Evonik Industries. In addition, silicone-free modified polyethers that do not have siloxane bonds, such as "BYK-UV3535" manufactured by BYK Japan Co., Ltd., can also be used.

[0042] The content of the polyether-modified polymer in the radiation-curable ink or the surface layer formed by such an ink is not particularly limited, and for example, from the viewpoint of expressing a low gloss appearance, it can be 0.5 parts by mass or more, 0.8 parts by mass or more, 1.0 parts by mass or more, 3.0 parts by mass or more, 5.0 parts by mass or more, 7.0 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more based on the total weight (solid content) of the ink or per 100 parts by mass of inorganic nanoparticles. There is no particular upper limit for the content of the polyether-modified polymer, and it can be, for example, 50 parts by mass or less, 40 parts by mass or less, 35 parts by mass or less, or 30 parts by mass or less.

[0043] Although the principle by which the use of polyether-modified polymers produces a low-gloss appearance due to radiation exposure is unclear, it is believed to be as follows. For example, considering the photograph in FIG. 4, it is believed that the surface energy of inorganic nanoparticles changes due to radiation exposure, and the polyether-modified polymer acts on the particle surface to promote the aggregation or crowding of inorganic nanoparticles. It is believed that the movement of aggregated or crowded inorganic nanoparticles toward the surface is caused by the fact that the curing speed of the radiation-curable oligomer or monomer near the surface of the surface layer is slower than the curing speed inside the surface layer due to the influence of oxygen in the atmosphere. In other words, it is believed that the aggregates of inorganic nanoparticles generated near the substrate side from the inside of the surface layer are immediately held in place by the cured binder resin component immediately after radiation exposure. On the other hand, it is believed that the aggregates near the surface of the surface layer can move to the surface area due to the slow curing speed of the radiation-curable oligomer, etc., even when exposed to radiation. As a result, it is believed that the migrated aggregates roughen the surface layer on the order of micrometers, and the inorganic nanoparticles that make up the aggregates also form fine irregularities on the order of nanometers on the surface of the surface layer, resulting in an excellent low-gloss appearance as shown in Figure 5(b).

[0044] In one embodiment, the surface layer of the present disclosure after irradiation with radiation can have a distribution (also called a "sea-island structure") of parts where inorganic nanoparticle aggregates are present (also called "island parts") and parts where they are not present (also called "sea parts"), as shown in Figure 4(b). For example, when the surface layer is prepared using an ink that already contains inorganic nanoparticle aggregates, the aggregates are generally distributed and arranged approximately uniformly in the surface layer, and such a surface layer does not exhibit a structure as shown in Figure 4(b), i.e., a structure in which the density of the aggregates is lower below, for example, in the middle part, than near the surface of the surface layer.

[0045] Here, in the present disclosure, the term "aggregate" refers to an aggregate or dense body in which, for example, 5 or more, 7 or more, or 10 or more primary particles of inorganic nanoparticles are gathered or densely packed, and the term "surface vicinity of the surface layer" refers to a region from the top of the surface of the surface layer to the bottom of the part in which inorganic nanoparticles are aggregated or densely arranged in the thickness direction. The density of the aggregates can be determined by measuring a cross section in the thickness direction of the surface layer using a scanning electron microscope (SEM). For example, the difference in the density of the aggregates can be determined by observing the presence or absence of a site formed in the surface vicinity of the surface layer where aggregates are densely arranged substantially continuously in the planar direction and thickness direction of the surface layer.

[0046] The radiation curable ink of the present disclosure contains at least one selected from a radiation curable polymerizable oligomer and a radiation curable polymerizable monomer.

[0047] In one embodiment, the radiation curable ink is advantageously a radical polymerization type (meth)acrylic ink employing a (meth)acrylic radiation curable polymerizable oligomer and a radiation curable polymerizable monomer from the viewpoints of compatibility with the compound of formula 1 described below, curing reactivity, etc. The surface layer formed using the (meth)acrylic ink is excellent in strength, weather resistance, etc., and is advantageous, for example, when the laminate is used as an interior material for a decorative film.

[0048] In one embodiment, the radiation curable ink contains a difunctional urethane (meth)acrylate oligomer, which is a radiation curable polymerizable oligomer, and optionally a radiation curable monofunctional monomer that can also function as a diluent. For example, in the inkjet printing method, it is difficult to purge with nitrogen due to the configuration of the device, and the ink is generally radiation cured in an air atmosphere. Compared to a multifunctional monomer having three or more functional groups, a difunctional or monofunctional monomer or oligomer is generally more susceptible to oxygen inhibition and tends to be difficult to cure in an air atmosphere. However, an ink containing a difunctional urethane (meth)acrylate oligomer is easily cured even in an air atmosphere, and the cured binder resin component has excellent elongation properties, etc., so that it is advantageous, for example, when the laminate is used as an interior material for a decorative film.

[0049] The bifunctional urethane (meth)acrylate oligomer is a urethane oligomer which is a reaction product of a diol and a diisocyanate, and has (meth)acryloyl groups introduced at both ends thereof. The (meth)acryloyl groups react with other bifunctional urethane (meth)acrylate oligomers and the (meth)acryloyl groups of the compound of formula 1 or monofunctional monomers to form a cured product. The bifunctional urethane (meth)acrylate oligomer can impart flexibility, impact resistance at low temperatures of about 0 to 10°C (sometimes simply referred to as "low-temperature impact resistance"), and chemical resistance to the cured product of the radiation-curable ink. The bifunctional urethane (meth)acrylate oligomer may be one type or a combination of two or more types. The diol and diisocyanate constituting the urethane oligomer may be one type or a combination of two or more types.

[0050] Diols include, for example, polyester polyols, polyether polyols, polycarbonate polyols, and polycaprolactone polyols.

[0051] The diol may include a low molecular weight diol, such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, bisphenol A, bisphenol F, hydrogenated bisphenol A, hydrogenated bisphenol F, 1,2-cyclopentanediol, and tricyclo[5.2.1.0]. 2,6 ]Decanedimethanol is an example.

[0052] The diisocyanate may be an aliphatic isocyanate or an aromatic isocyanate. Examples of the aliphatic isocyanate include tetramethylene diisocyanate, hexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, decamethylene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, and 4,4'-methylenebis(cyclohexylisocyanate). Examples of aromatic isocyanates include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, methylene diphenyl 4,4'-diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, diphenylmethane-2,2'-diisocyanate, diphenylmethane-2,4'-diisocyanate, 4,4'-diisocyanato-3,3'-dimethylbiphenyl, 1,5-naphthalene diisocyanate, and 2-methyl-1,5-naphthalene diisocyanate.

[0053] By using aliphatic compounds as both the diol and the diisocyanate, it is possible to improve the weather resistance of the cured product of the radiation curable ink, and the surface layer containing the cured product.

[0054] The introduction of the (meth)acryloyl group can be carried out by reacting the isocyanato terminal of the urethane oligomer with a hydroxyl group-containing (meth)acrylate. Examples of the hydroxyl group-containing (meth)acrylate include 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl acrylate, 2-hydroxybutyl methacrylate, dipropylene glycol monoacrylate, and dipropylene glycol monomethacrylate. The hydroxyl group-containing (meth)acrylate can be used alone or in combination of two or more. In this embodiment, it is desirable to use an excess of diisocyanate relative to the diol during the synthesis of the urethane oligomer, that is, to make the molar ratio of NCO group / OH group greater than 1.

[0055] The introduction of the (meth)acryloyl group can also be carried out by reacting the hydroxyl group terminal of the urethane oligomer with an isocyanato group-containing (meth)acrylate. Examples of the isocyanato group-containing (meth)acrylate include 2-isocyanatoethyl acrylate and 2-isocyanatoethyl methacrylate. In this embodiment, it is desirable to use an excess of diol relative to diisocyanate during the synthesis of the urethane oligomer, that is, to set the molar ratio of NCO group / OH group to less than 1.

[0056] Examples of the difunctional urethane (meth)acrylate oligomer include polyester urethane di(meth)acrylate oligomer, polycarbonate urethane di(meth)acrylate oligomer, and polyether urethane di(meth)acrylate oligomer.

[0057] The difunctional urethane (meth)acrylate oligomer is advantageously a difunctional aliphatic urethane acrylate oligomer from the viewpoints of curability in an air atmosphere, elongation characteristics, etc. The difunctional aliphatic urethane acrylate oligomer can provide a cured product having excellent weather resistance and a surface layer containing such a cured product.

[0058] The number average molecular weight Mn of the bifunctional urethane (meth)acrylate oligomer can be 500 or more, 1,000 or more, or 1,200 or more, and 5,000 or less, 4,000 or less, or 3,000 or less. The weight average molecular weight Mw of the bifunctional urethane (meth)acrylate oligomer can be 500 or more, 1,000 or more, or 1,200 or more, and 5,000 or less, 4,000 or less, or 3,000 or less. The number average molecular weight Mn and the weight average molecular weight Mw are values ​​calculated using standard polystyrene by gel permeation chromatography.

[0059] The radiation curable ink preferably contains 20 parts by mass or more, 25 parts by mass or more, or 30 parts by mass or more of the bifunctional urethane (meth)acrylate oligomer based on 100 parts by mass of the radiation curable component. By making the content of the bifunctional urethane (meth)acrylate oligomer 20 parts by mass or more based on 100 parts by mass of the radiation curable component, the flexibility, low-temperature impact resistance, and chemical resistance of the cured product of the radiation curable ink can be further improved. The radiation curable ink preferably contains 50 parts by mass or less, 45 parts by mass or less, or 40 parts by mass or less of the bifunctional urethane (meth)acrylate oligomer based on 100 parts by mass of the radiation curable component. By making the content of the bifunctional urethane (meth)acrylate oligomer 50 parts by mass or less based on 100 parts by mass of the radiation curable component, good inkjet ejection properties or coating properties can be obtained. In this disclosure, the term "radiation-curable component" includes difunctional urethane (meth)acrylate oligomers, other radiation-curable polymerizable monomers and oligomers such as monofunctional monomers having a dioxane moiety or dioxolane moiety described below, and compounds of formula 1 described below.

[0060] In some embodiments, the radiation curable ink can include other radiation curable polymerizable oligomers or monomers, such as monofunctional monomers having a dioxane or dioxolane moiety, and such other radiation curable polymerizable oligomers and monomers can be used alone or in combination.

[0061] The monofunctional monomer having a dioxane moiety or a dioxolane moiety is a compound having at least one of a dioxane moiety and a dioxolane moiety in the molecule and having only one reactive functional group. When the monofunctional monomer having a dioxane moiety or a dioxolane moiety is used in combination with a bifunctional urethane (meth)acrylate oligomer, it can enhance the low-temperature impact resistance of the cured product and the surface layer containing the cured product. Examples of the reactive functional group include a (meth)acryloyl group, a (meth)acrylamide group, and a vinyl group. Since the monofunctional monomer having a dioxane moiety or a dioxolane moiety has a high reactivity with the bifunctional urethane (meth)acrylate oligomer, it is advantageous for the monofunctional monomer having a dioxane moiety or a dioxolane moiety to have a (meth)acryloyl group, particularly an acryloyl group. The monofunctional monomer having a dioxane moiety or a dioxolane moiety may be one type or a combination of two or more types.

[0062] Examples of monofunctional monomers having a dioxane moiety or a dioxolane moiety include monofunctional monomers having a dioxane moiety, such as (5-ethyl-1,3-dioxane-5-yl)methyl (meth)acrylate (also called cyclic trimethylolpropane formal acrylate), (2-methyl-5-ethyl-1,3-dioxane-5-yl)methyl (meth)acrylate, (2,2-dimethyl-5-ethyl-1,3-dioxane-5-yl)methyl (meth)acrylate, (2-methyl-2,5-diethyl-1,3-dioxane-5-yl)methyl (meth)acrylate, (2,2,5-triethyl-1,3-dioxane-5-yl)methyl (meth)acrylate, (2,5-diethyl-1,3-dioxane-5-yl)methyl (meth)acrylate, and polyethylene glycol (meth)acrylate having a 1,3-dioxane ring. Functional monomers, and (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-cyclohexyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2,2-dimethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-isobutyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, Examples of monofunctional monomers having a dioxolane moiety include (2-oxo-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-oxo-1,3-dioxolan-4-yl)methyl (meth)acrylate, 2-(2-oxo-1,3-dioxolan-4-yl)ethyl (meth)acrylate, and 3-(2-oxo-1,3-dioxolan-4-yl)propyl (meth)acrylate.

[0063] The monofunctional monomer having a dioxane or dioxolane moiety is preferably (5-ethyl-1,3-dioxan-5-yl)methyl (meth)acrylate or (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, more preferably (5-ethyl-1,3-dioxan-5-yl)methyl acrylate or (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate because of its high reactivity with the bifunctional urethane (meth)acrylate oligomer, and particularly preferably (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate because of its excellent low-temperature impact resistance.

[0064] The radiation curable ink preferably contains 10 parts by mass or more, 20 parts by mass or more, or 30 parts by mass or more of a monofunctional monomer having a dioxane or dioxolane moiety, based on 100 parts by mass of the radiation curable component, and preferably 80 parts by mass or less, 70 parts by mass or less, or 50 parts by mass or less. By making the content of the monofunctional monomer having a dioxane or dioxolane moiety 10 parts by mass or more based on 100 parts by mass of the radiation curable component, good low-temperature impact resistance can be obtained. By making the content of the monofunctional monomer having a dioxane or dioxolane moiety 80 parts by mass or less based on 100 parts by mass of the radiation curable component, good weather resistance can be obtained.

[0065] In some embodiments, the radiation-curable ink may contain other radiation-curable polymerizable monomers, such as, for example, chain alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isoamyl (meth)acrylate, 2-methylbutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate; alicyclic (meth)acrylates such as cyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; and phenoxyethyl (meth)acrylate. phenoxyalkyl (meth)acrylates such as methoxypropyl (meth)acrylate, 2-methoxybutyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxypropyl (meth)acrylate, 2-methoxybutyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate; cyclic ether-containing (meth)acrylates such as glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate; hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate; nitrogen-containing (meth)acrylamide, N,N-diethyl (meth)acrylamide, and other monofunctional monomers. Other examples of radiation-curable polymerizable monomers include monofunctional monomers such as vinyl compounds, such as vinyl acetate, vinyl propionate, styrene, and vinyl toluene; unsaturated nitriles, such as acrylonitrile and methacrylonitrile; and unsaturated carboxylic acids, such as crotonic acid, itaconic acid, fumaric acid, citraconic acid, and maleic acid. Among these, from the viewpoints of the expression of a low gloss appearance after radiation exposure, low ink viscosity, storage stability, and the like, n-octyl (meth)acrylate and trimethylcyclohexyl (meth)acrylate are preferred, and it is more preferred to use these in combination.

[0066] The other radiation curable polymerizable monomer may be a polyfunctional monomer. The polyfunctional monomer functions as a crosslinking agent to increase the strength and durability of the cured product. Crosslinking using the polyfunctional monomer may increase the adhesion between the surface layer containing the cured product and the substrate or other layers on the surface layer. From the viewpoint of elongation properties and impact resistance, the content of the polyfunctional monomer is preferably 5 parts by mass or less, or 3 parts by mass or less, based on 100 parts by mass of the radiation curable component.

[0067] Examples of the polyfunctional monomer include bifunctional (meth)acrylates such as 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate; trifunctional (meth)acrylates such as glycerol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol tri(meth)acrylate; and (meth)acrylates having four or more functional groups such as ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and pentaerythritol tetra(meth)acrylate.

[0068] For example, other radiation-curable polymerizable monomers having a (meth)acryloyl group, particularly an acryloyl group, are advantageous because they have high reactivity with bifunctional urethane (meth)acrylate oligomers and monofunctional monomers having any dioxane or dioxolane moiety, and form cured products that have excellent adhesion to other materials such as the base layer and decorative layer.

[0069] In some embodiments, the radiation curable ink is free of other radiation curable polymerizable monomers, including the monofunctional and polyfunctional monomers described above, or can include more than 0 parts, 10 parts or more, or 20 parts or more by weight of such radiation curable polymerizable monomers, based on 100 parts by weight of the radiation curable component, and can include 70 parts or less, 60 parts or less, or 50 parts or less by weight of such radiation curable polymerizable monomers.

[0070] As radiation-curable polymerizable oligomers other than the bifunctional urethane (meth)acrylate oligomer, for example, polyester (meth)acrylate, epoxy (meth)acrylate, etc. can be used. These radiation-curable polymerizable oligomers may be monofunctional or polyfunctional.

[0071] In some embodiments, the radiation curable ink can contain no other radiation curable polymerizable oligomers, or can contain more than 0 parts by weight, 5 parts or more, or 10 parts or more by weight of such radiation curable polymerizable oligomers, based on 100 parts by weight of the radiation curable component, and can contain 50 parts or less, 40 parts or less, or 30 parts or less by weight.

[0072] In some embodiments, the total content of other radiation curable multifunctional monomers and radiation curable multifunctional oligomers in the radiation curable ink can be 30 parts by weight or less, 20 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, 3 parts by weight or less, or 1 part by weight or less based on 100 parts by weight of the radiation curable component, or these multifunctional monomers and multifunctional oligomers can be not blended in the ink. By not using multifunctional monomers and multifunctional oligomers or by making the total content 10 parts by weight or less, it is possible to improve the migration of inorganic nanoparticles to the surface of the aggregates and to increase the flexibility or elongation properties of the cured product.

[0073] As the photopolymerization initiator, for example, a known compound capable of inducing a radical polymerization reaction can be used. As the photopolymerization initiator, either an intramolecular cleavage type or a hydrogen abstraction type can be used, and examples thereof include 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethylbenzoyldiphenylphosphine oxide, benzoyldiethoxyphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, benzoin alkyl ethers (e.g., benzoin methyl ether, Benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, n-butyl benzoin ether, etc.), methyl benzoyl formate, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, p-tert-butyl trichloroacetophenone, p-tert-butyl dichloroacetophenone, benzil, acetophenone, thioxanthone compounds (2-chlorothioxanthone, 2-methylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone), camphorquinone, 3-ketocoumarin, anthraquinone compounds (e.g., anthraquinone, 2-ethylanthraquinone, α-chloroanthraquinone, 2-tert-butylanthraquinone, etc.), acenaphthene, 4,4'-dimethoxybenzyl, and 4,4'-dichlorobenzyl. The photopolymerization initiators can be used alone or in combination of two or more kinds.

[0074] In some embodiments, the radiation curable ink can include 1 part or more, or 2 parts or more, and can include 20 parts or less, or 15 parts or less, by weight of a photoinitiator, based on 100 parts by weight of the radiation curable component.

[0075] In some embodiments, the radiation curable inks of the present disclosure can include a compound of Formula 1, shown below:

[0076] For example, in inkjet printing, inkjet ink is generally discharged from a discharge nozzle and applied to a substrate, and the required performance of the ink includes, for example, low viscosity and low clogging with few foreign matter. When inorganic nanoparticles are simply contained in the ink, the ink generally tends to have a high viscosity in the opposite direction to the required performance, and the ink tends to clog due to aggregation of the nanoparticles. Under such circumstances, the present inventor has found that by using a compound of formula 1 described later in combination with inorganic nanoparticles, the ink viscosity can be reduced to a level that allows printing or coating by inkjet printing, gravure coating, bar coating, etc., while reducing or suppressing the aggregation and coalescence of inorganic nanoparticles in the ink.

[0077] The compound of formula 1 can be represented by the following chemical formula: R 1 -R 2 -Si(OR 3 )3...Formula 1

[0078] In the formula, R 1 is an acryloyl group or a methacryloyl group, R 2 is an alkylene group having 5 to 12 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms. From the viewpoint of reducing viscosity, R 1 is preferably a methacryloyl group, R 2 is preferably an alkylene group having 6 to 10 carbon atoms, more preferably an alkylene group having 8 to 10 carbon atoms; R 3is preferably an alkyl group having 1 to 3 carbon atoms, more preferably an alkyl group having 1 to 2 carbon atoms. Among them, 8-(meth)acryloxyoctyltrimethoxysilane is particularly preferable as the compound of formula 1. The compound represented by formula 1 can be used alone or in combination of two or more kinds.

[0079] The reason why the compound of formula 1 can reduce the viscosity of the ink is unclear, but R 2 This is believed to be due to the fact that the chain length of R is longer than that of general silane coupling agents. 2 It is believed that the particles are less likely to come into close contact with each other due to the presence of these particles, improving their fluidity and thereby reducing the viscosity of the ink.

[0080] There is no particular limit to the amount of the compound of formula 1. Although this compound is a type of silane coupling agent, unlike general silane coupling agents, it is not used to improve adhesion to substrates, etc., but is used to reduce viscosity, so its amount can be lower than that of general silane coupling agents. For example, the amount of the compound of formula 1 can be 0.030 mmol or more, 0.040 mmol or more, or 0.050 mmol or more per 1 g of inorganic nanoparticles from the viewpoint of reducing viscosity, and can be 0.090 mmol or less, 0.080 mmol or less, or 0.070 mmol or less.

[0081] In some embodiments, the radiation curable ink of the present disclosure may further include a non-functional silane coupling agent, which may also contribute to lowering the viscosity of the ink.

[0082] The compound of formula 1 is R 1Since the compound has an acryloyl group or a methacryloyl group as a substituent, it can form a crosslinked structure with, for example, the radiation-curable polymerizable oligomer and / or the radiation-curable polymerizable monomer in the ink by radiation, which can improve the hardness or abrasion resistance of the surface layer, but can also reduce the elongation properties required for, for example, decorative films. When it is desired to impart elongation properties by reducing the viscosity of the ink and reducing the formation of crosslinked structures, it is advantageous to use the compound of formula 1 in combination with a non-functional silane coupling agent.

[0083] There is no particular limitation on such non-functional silane coupling agents, but examples thereof include n-propyltrimethoxysilane, isopropyltrimethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, n-pentyltrimethoxysilane, isopentyltrimethoxysilane, n-hexyltrimethoxysilane, isohexyltrimethoxysilane, n-heptyltrimethoxysilane, isoheptyltrimethoxysilane, n-octyltrimethoxysilane, and isooctyltrimethoxysilane. Among these, n-propyltrimethoxysilane, n-hexyltrimethoxysilane, and isooctyltrimethoxysilane are preferred, and isooctyltrimethoxysilane is more preferred. These can be used alone or in combination of two or more.

[0084] The amount of the non-functional silane coupling agent is not particularly limited, but similarly to the compound of formula 1, from the viewpoint of reducing viscosity, the amount can be 0.030 mmol or more, 0.040 mmol or more, or 0.050 mmol or more per 1 g of inorganic nanoparticles, and can be 0.090 mmol or less, 0.080 mmol or less, or 0.070 mmol or less.

[0085] In order to reduce the viscosity of the ink, it is generally diluted by blending an organic or aqueous solvent, but for example, the use of an organic solvent deteriorates the working environment, and any solvent requires a drying process after printing or coating, which tends to deteriorate productivity. When an ink containing a large amount of solvent is printed on a resin substrate, for example, by an inkjet printing method, the ink that has landed tends to wet and spread on the substrate surface, so that the intended printing performance may not be fully exhibited. On the other hand, if the ink is a solvent-free ink, the ink that has landed tends not to wet and spread on the substrate surface, so that good printing performance can be exhibited, and for example, a texture with a real texture or a three-dimensional unevenness that matches the design of a decorative film or the like can be imparted to the substrate surface. Since the radiation-curable ink of the present disclosure can achieve low viscosity using the specific compound of formula 1 described above and optionally a non-functional silane coupling agent, the content of the solvent can be 5% by mass or less, 3% by mass or less, or 1% by mass or less based on the total amount of the ink, or the ink may not contain a solvent.

[0086] For example, in the case of a conventional ink containing a high content of solvent and microbeads, when the ink is applied to the surface of a substrate to form a surface layer, and then the solvent in the surface layer is dried, the volume of the surface layer is reduced and some of the microbeads are precipitated on the surface of the surface layer, which makes it easy to develop a low gloss appearance. However, when the content of the solvent in the ink is 5% by mass or less, the volume reduction effect of the surface layer is not developed, and it is difficult to precipitate some of the microbeads on the surface of the surface layer, so that it is difficult to develop a low gloss appearance. In this case, for example, it is possible to adopt beads that are larger than the thickness of the surface layer, but ink containing beads of such a size is likely to clog inkjet nozzles, etc. On the other hand, the radiation-curable ink of the present disclosure can develop a low gloss appearance by irradiating radiation onto the surface layer applied to the substrate, even if the content of the solvent in the ink is 5% by mass or less.

[0087] The radiation curable ink may contain, as optional components, additives such as light stabilizers, polymerization inhibitors, UV absorbers, defoamers, antifouling agents, surface conditioners, pigments, and dyes.

[0088] The radiation-curable ink of the present disclosure can achieve a low gloss appearance without using beads used in conventional inks, such as micrometer-order resin beads or glass beads, and does not preclude the use of such beads. When such beads are used, the amount of beads used can be, for example, 10% by mass or less, 7% by mass or less, 5% by mass or less, 3% by mass or less, or 1% by mass or less based on the total weight (solids content) of the ink or the total weight (dry coating weight) of the surface layer.

[0089] A surface layer prepared by using the radiation-curable ink of the present disclosure and irradiating it with radiation can exhibit an excellent low gloss appearance.

[0090] The low gloss appearance of the surface layer can be evaluated, for example, by the 60-degree surface gloss when the measurement angle is 60 degrees. The 60-degree surface gloss can be 50.0GU or less, 40.0GU or less, 30.0GU or less, 20.0GU or less, or 15.0GU or less. There is no particular limit to the lower limit of the 60-degree surface gloss, but it can be, for example, 1.0GU or more, 3.0GU or more, or 5.0GU or more. The surface gloss in the present disclosure is measured using a portable gloss meter BYK Gardner Micro-Tri-Gloss (BYK Japan Co., Ltd.) in accordance with JIS Z8741. This surface gloss is a value measured on the surface layer in a state where mechanical means such as embossing have not been applied.

[0091] In some embodiments, the surface gloss of the surface layer of the laminate can be evaluated by the 20-degree surface gloss when the measurement angle is 20 degrees. The 20-degree surface gloss can be 20.0GU or less, 15.0GU or less, or 10.0GU or less. There is no particular limit to the lower limit of the 20-degree surface gloss, but it can be, for example, 0.1GU or more, 0.3GU or more, or 0.5GU or more.

[0092] In some embodiments, the surface gloss of the surface layer of the laminate can be evaluated by the 80-degree surface gloss when the measurement angle is 80 degrees. The 80-degree surface gloss can be 90.0GU or less, 85.0GU or less, or 80.0GU or less. There is no particular limit to the lower limit of the 80-degree surface gloss, but it can be, for example, 10.0GU or more, 13.0GU or more, or 15.0GU or more.

[0093] In some embodiments, the initial viscosity of the radiation-curable ink may be, for example, 35.0 mPa·s or less, 30.0 mPa·s or less, 25.0 mPa·s or less, 20.0 mPa·s or less, 18.0 mPa·s or less, 17.0 mPa·s or less, 16.0 mPa·s or less, 15.0 mPa·s or less, 14.0 mPa·s or less, 13.0 mPa·s or less, or 12.0 mPa·s or less at 55° C. in terms of ejection properties from an inkjet nozzle, coating properties, and the like. There is no particular restriction on the lower limit of the initial viscosity, but in terms of printability and the like, it may be, for example, 1.0 mPa·s or more, 3.0 mPa·s or more, or 5.0 mPa·s or more. A radiation-curable ink having such a viscosity range may be prepared, for example, by using the compound of formula 1 described above and / or a non-functional silane coupling agent.

[0094] In some embodiments, the radiation-curable ink of the present disclosure has excellent storage stability at high temperatures. Such storage stability can be indirectly evaluated by the viscosity at 55°C after storing the ink at 60°C for one week. The radiation-curable ink of one embodiment of the present disclosure can achieve a viscosity at 55°C after storing at 60°C for one week of 30.0 mPa·s or less, 25.0 mPa·s or less, 20.0 mPa·s or less, 18.0 mPa·s or less, 17.0 mPa·s or less, 16.0 mPa·s or less, 15.0 mPa·s or less, 14.0 mPa·s or less, 13.0 mPa·s or less, or 12.0 mPa·s or less. There is no particular restriction on the lower limit of such viscosity, but it can be, for example, 1.0 mPa·s or more, 3.0 mPa·s or more, or 5.0 mPa·s or more.

[0095] The surface layer can be formed by applying a radiation-curable ink directly or via another layer onto a substrate by various printing or coating methods, and curing the ink by irradiating it with radiation such as ultraviolet light or electron beams. When irradiating with radiation, it is generally performed in a nitrogen atmosphere to prevent a decrease in the curing rate or poor curing caused by oxygen. However, as described above, if the curing rate of the radiation-curable oligomer near the surface of the surface layer differs from the curing rate inside, it is considered that the aggregates of inorganic nanoparticles tend to move toward the surface, so it is advantageous to irradiate with radiation in an air atmosphere containing oxygen. For example, in the inkjet printing method, it is difficult to perform nitrogen purging due to the configuration of the device, and the ink is generally radiation-cured in an air atmosphere, so the radiation-curable ink of the present disclosure can be suitably used for the inkjet printing method.

[0096] Generally, a high-viscosity ink is easy to reduce or suppress the aggregation and coalescence of inorganic particles in the ink, while a low-viscosity ink is difficult to reduce or suppress the aggregation and coalescence of inorganic particles. The radiation-curable ink of the present disclosure is low-viscosity yet can reduce or suppress the aggregation and coalescence of inorganic nanoparticles in the ink, and therefore can be used for various printing or coating methods that require the use of low-viscosity ink, such as inkjet printing, gravure coating, bar coating, knife coating, capillary coating, spray coating, and stereolithography (sometimes referred to as "layered modeling"). Among them, the radiation-curable ink of the present disclosure can be suitably used for inkjet printing, which is easily affected by aggregates. The surface layer prepared by such a method can be distinguished from, for example, an inkjet printing surface layer, a gravure coating surface layer, and the like.

[0097] The radiation curable ink may be printed or coated on at least a portion of the substrate, or may be printed or coated on the entire substrate. The surface layer before radiation exposure may have a substantially smooth surface, or may have an uneven surface such as an embossed pattern. When such a surface layer is irradiated with radiation, fine unevenness on the nanometer order and unevenness on the micrometer order based on inorganic nanoparticles can be formed on the surface of the surface layer, which differs from uneven surfaces such as an embossed pattern.

[0098] The thickness of the surface layer is not particularly limited, and can be appropriately adjusted depending on the expression of a low gloss appearance after radiation exposure, the design, etc. For example, the thickness of the surface layer can be at least partially 7 micrometers or more, 20 micrometers or more, or 30 micrometers or more. By providing a portion of the surface layer having a thickness of 7 micrometers or more, for example, when the laminate is used as a decorative film, a texture having a real texture or three-dimensional unevenness matching the design of the decorative film can be imparted to the surface of the decorative film.

[0099] In some embodiments, the maximum thickness of the surface layer can be, for example, 500 micrometers or less, 300 micrometers or less, or 100 micrometers or less. By making the maximum thickness of the surface layer 500 micrometers or less, the flexibility of the surface layer, such as elongation and bending properties, can be made suitable.

[0100] The thickness of the surface layer can be appropriately adjusted, for example, by repeatedly printing or coating a radiation-curable ink locally or all over the surface. Here, the thickness of each layer in the laminate of the present disclosure can be defined as the average value of thicknesses at any of at least five locations in the target layer of the laminate, for example, the surface layer, measured using a scanning electron microscope (SEM) in the thickness direction of the laminate.

[0101] The surface layer may be wholly or partially transparent, semi-transparent, or opaque in the visible range to provide the desired appearance.

[0102] The substrate constituting the laminate of the present disclosure can be used, for example, as a support for the surface layer. The surface of the substrate may be subjected to a surface treatment such as a corona treatment or a plasma treatment.

[0103] The material of the substrate is not particularly limited, and various resin materials, for example, polyvinyl chloride resin, polyurethane resin, polyolefin resin such as polyethylene (PE) and polypropylene (PP), polyester resin such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polycarbonate resin, polyimide resin, polyamide resin, (meth)acrylic resin such as polymethyl methacrylate (PMMA), fluororesin, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer, ethylene-ethyl acrylate copolymer, ethylene-vinyl acetate copolymer, acrylonitrile-butadiene rubber (NBR), acrylonitrile-butadiene-styrene copolymer (ABS), and other copolymers, can be mentioned. These can be used alone or in combination of two or more. Inorganic substrates such as glass and metal substrates such as aluminum can also be used as the substrate.

[0104] The shape or configuration of the substrate is not particularly limited, and may be, for example, a film shape, a plate shape, a curved shape, an irregular shape, or a three-dimensional shape, and may be a single-layer structure, a laminated structure, or a composite structure in which multiple substrates of different shapes are combined.

[0105] The substrate may be colored or colorless. The substrate may be opaque, translucent, or transparent. The substrate may have a generally smooth surface or a structured surface, which may be formed by a surface treatment such as embossing.

[0106] The thickness of the substrate may be, for example, 50 micrometers or more, 80 micrometers or more, or 100 micrometers or more. There is no particular upper limit to the thickness, but from the viewpoint of tracking ability, production costs, etc., the thickness may be, for example, 500 micrometers or less, 300 micrometers or less, or 200 micrometers or less.

[0107] In some embodiments, the laminate of the present disclosure may further include at least one selected from the group consisting of a decorative layer, a glittering layer, a bonding layer, an adhesive layer, and a release liner, depending on the intended use, etc. In the present disclosure, for example, a laminate including a colored substrate and / or surface layer, or a laminate including a decorative layer and / or a glittering layer may be referred to as a decorative film.

[0108] In the laminate of the present disclosure, for example, a decorative layer can be disposed above or below the substrate. The decorative layer can be applied, for example, to the entire surface or a part of the substrate.

[0109] Examples of decorative layers include, but are not limited to, color layers having paint colors, for example, light colors such as white and yellow, and dark colors such as red, brown, green, blue, gray, and black; pattern layers that impart patterns such as wood grain, stone grain, geometric patterns, and leather patterns, logos, and designs to articles; relief layers having an uneven surface; and combinations of these.

[0110] Materials for the color layer are not limited to the following, but may include, for example, inorganic pigments such as carbon black, yellow lead, yellow iron oxide, red iron oxide, and red iron oxide; phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green; organic pigments such as azo lake pigments, indigo pigments, perinone pigments, perylene pigments, quinophthalone pigments, dioxazine pigments, and quinacridone pigments such as quinacridone red, dispersed in a binder resin such as (meth)acrylic resin or polyurethane resin.

[0111] The color layer can be formed using such materials by a coating method such as gravure coating, roll coating, die coating, bar coating, or knife coating, or can also be formed by a printing method such as inkjet printing.

[0112] The pattern layer is not limited to the following, but may be, for example, a pattern such as a design, logo, or picture directly applied to a substrate or the like using a printing method such as gravure direct printing, gravure offset printing, inkjet printing, laser printing, or screen printing, or may be a film or sheet having a pattern, logo, or picture formed by coating such as gravure coating, roll coating, die coating, bar coating, or knife coating, punching, etching, or the like. The material of the pattern layer may be, for example, the same material as that used for the color layer.

[0113] The relief layer may be a thermoplastic resin film having a surface texture formed by a conventional method such as embossing, scratching, laser processing, dry etching, or hot pressing. The relief layer may also be formed by applying a thermosetting or radiation curing resin such as a curable (meth)acrylic resin onto a release liner having a texture, curing the resin by heating or irradiating it with radiation, and removing the release liner.

[0114] The thermoplastic resin, thermosetting resin, and radiation curable resin used in the relief layer are not particularly limited, and examples thereof include fluororesins, polyester resins such as PET and PEN, (meth)acrylic resins, polyolefin resins such as polyethylene and polypropylene, thermoplastic elastomers, polycarbonate resins, polyamide resins, ABS resins, acrylonitrile-styrene resins, polystyrene resins, vinyl chloride resins, polyurethane resins, etc. The relief layer may contain at least one of the pigments used in the color layer.

[0115] The thickness of the decorative layer may be appropriately adjusted depending on the required decorativeness, hiding property, etc., and is not particularly limited, but can be, for example, 1 micrometer or more, 3 micrometers or more, or 5 micrometers or more, and can be 50 micrometers or less, 40 micrometers or less, 30 micrometers or less, 20 micrometers or less, or 15 micrometers or less.

[0116] The luminous layer is not limited to the following, but may be, for example, a layer containing a metal selected from aluminum, nickel, gold, silver, copper, platinum, chromium, iron, tin, indium, titanium, lead, zinc, germanium, etc., or an alloy or compound thereof, formed on the entire surface or part of the base material or decorative layer by vacuum deposition, sputtering, ion plating, plating, etc. The thickness of the luminous layer can be appropriately selected depending on the required decorativeness, brightness, etc.

[0117] A bonding layer (sometimes called a "primer layer") may be used to bond the layers constituting the laminate. As the bonding layer, for example, a commonly used (meth)acrylic, polyolefin, polyurethane, polyester, rubber, or other solvent-based, emulsion-based, pressure-sensitive, heat-sensitive, thermosetting, or UV-curable adhesive can be used. The bonding layer can be applied by a known coating method or the like.

[0118] The thickness of the bonding layer can be, for example, 0.05 micrometers or more, 0.5 micrometers or more, or 5 micrometers or more, and can be 100 micrometers or less, 50 micrometers or less, 20 micrometers or less, or 10 micrometers or less.

[0119] The laminate may further include an adhesive layer for attaching the laminate to the adherend. The adhesive layer may be made of a material similar to that of the bonding layer. The adhesive layer may be applied to the adherend instead of the laminate.

[0120] The thickness of the adhesive layer can be, for example, but not limited to, 5 micrometers or more, 10 micrometers or more, or 20 micrometers or more, and can be 200 micrometers or less, 100 micrometers or less, or 80 micrometers or less.

[0121] The base material, decorative layer, bonding layer and adhesive layer of the present disclosure may contain optional components such as fillers, reinforcing materials, antioxidants, UV absorbers, light stabilizers, heat stabilizers, tackifiers, dispersants, plasticizers, flow improvers, surfactants, leveling agents, silane coupling agents, catalysts, pigments, dyes and the like, within the scope of not impairing the effects and decorativeness of the present disclosure.

[0122] Any suitable release liner can be used to protect the adhesive layer.Representative release liners include those prepared from paper (e.g., kraft paper), polymer materials (e.g., polyolefins such as polyethylene or polypropylene, polyesters such as ethylene vinyl acetate, polyurethane, polyethylene terephthalate, etc.), etc.The release liner may be coated with a layer of a release agent such as a silicone-containing material or a fluorocarbon-containing material, if necessary.

[0123] The thickness of the release liner can be, for example, 5 micrometers or more, 15 micrometers or more, or 25 micrometers or more, and can be 300 micrometers or less, 200 micrometers or less, or 150 micrometers or less. The thickness of the release liner can be defined as the average value calculated by measuring the thickness of any part of the release liner at least five times using a high-precision Digimatic Micrometer (MDH-25MB, manufactured by Mitutoyo Corporation) after removing the release liner from the adhesive layer.

[0124] The laminate of the present disclosure can be prepared as appropriate by known methods, for example, printing methods such as inkjet printing, gravure direct printing, gravure offset printing, and screen printing, coating methods such as gravure coating, roll coating, die coating, bar coating, knife coating, and extrusion coating, lamination methods, transfer methods, and the like, either alone or in combination.

[0125] The product form of the laminate of the present disclosure is not particularly limited, and may be, for example, a discrete product such as a sheet, a laminate in which a plurality of sheets are stacked, or a roll in which a sheet is wound into a roll.

[0126] In some embodiments, the surface layer of the present disclosure is extensible, and a laminate having this surface layer can exhibit excellent elongation properties. Such elongation properties can be evaluated, for example, by an elongation at break test. The surface layer of the laminate of some embodiments can exhibit an elongation at break of 50% or more, 70% or more, 80% or more, 85% or more, or 90% or more at 20°C. There is no particular limit to the upper limit of the elongation at break, but it can be, for example, 200% or less, 180% or less, 160% or less, or 150% or less. Break refers to the occurrence of a visually recognizable change in appearance, such as a crack or gloss change, on the surface of the surface layer. A laminate having such elongation properties can be suitably used, for example, as a decorative film.

[0127] In the elongation at break test, the laminate is cut to a length of 100 mm and a width of 25 mm to prepare a test sample, and a tensile tester (Tensilon universal testing machine, model number: RTC-1210A, manufactured by A&D Co., Ltd.) is used to measure the elongation at the time when the surface layer of the test sample breaks at a clamp distance of 50 mm, a tensile speed of 300 mm / min, and 20°C. The elongation at break is determined by the formula: (length of test sample at break - length of test sample before elongation) / (length of test sample before elongation) x 100(%).

[0128] The use of the laminate of the present disclosure is not particularly limited. For example, the laminate of the present disclosure can be used for decorative purposes, optical purposes, and the like. For example, the laminate of the present disclosure can be used as interior materials such as inner walls, stairs, windows, doors, floors, ceilings, pillars, and partitions of buildings, condominiums, houses, and other structures, or as exterior materials such as exterior walls, and can be used as various interior or exterior products, for example, interior or exterior products of vehicles such as automobiles, railways, aircraft, and ships. In addition, it can be used for electrical appliances such as personal computers, smartphones, mobile phones, refrigerators, and air conditioners, stationery, furniture, desks, various containers such as cans, road signs, signboards, and the like. Furthermore, the laminate of the present disclosure can also be used as a light diffusion member used in display devices such as liquid crystal displays and organic EL display devices, for example, a light diffusion film or light diffusion plate for ensuring uniformity of the luminance of the backlight, or an antiglare (AG) film for reducing or preventing reflection of light from fluorescent lamps, and the like. EXAMPLES

[0129] The following examples illustrate specific embodiments of the disclosure, but do not limit the invention. All parts and percentages are by weight unless otherwise specified.

[0130] The materials, reagents, etc. used in this example are shown in Table 1.

[0131] [Table 1]

[0132] Preparation of Surface-Modified Silica Sol The surface-modified silica sol was prepared by the following method.

[0133] (Sol 1) 0.452g of KBM5803, 0.832g of isooctyltrimethoxysilane, and 0.0045g of 4-hydroxy-TEMPO free radical were added to a glass bottle containing 30g of IPA. This mixture was added to a glass bottle containing 150g of IPA-ST-ZL and stirred at room temperature for 10 minutes. The glass bottle was sealed and placed in an oven at 60°C for 16 hours. This mixture was then poured into a flask and mixed with 113.40g of Viscoat™ 196. Next, IPA was removed from the resulting mixture using a rotary evaporator while heating to 55°C until the solid content of the mixture was around 30% by mass. Then, Viscoat™ 196 was added to this mixture so that the concentration of silica nanoparticles was 28.94% by mass, to prepare Sol 1.

[0134] (Zol 2) 0.8927g of KBM5803, 1.6423g of isooctyltrimethoxysilane, and 0.0089g of 4-hydroxy-TEMPO free radical were added to a glass bottle containing 30g of IPA. This mixture was added to a glass bottle containing 150g of IPA-ST-L and stirred at room temperature for 10 minutes. The glass bottle was sealed and placed in an oven at 60°C for 16 hours. This mixture was then poured into a flask and mixed with 114.90g of Viscoat™ 196. Next, IPA was removed from the resulting mixture using a rotary evaporator while heating to 55°C until the solid content of the mixture was around 30% by mass. Then, Viscoat™ 196 was added to this mixture so that the concentration of silica nanoparticles was 29.21% by mass, to prepare Sol 2.

[0135] (Zol 3) 1.8817g of KBM5803, 3.4618g of isooctyltrimethoxysilane, and 0.0188g of 4-hydroxy-TEMPO free radical were added to a glass bottle containing 30g of IPA. This mixture was added to a glass bottle containing 150g of IPA-ST and stirred at room temperature for 10 minutes. The glass bottle was sealed and placed in an oven at 60°C for 16 hours. This mixture was then poured into a flask and mixed with 123.65g of Viscoat™ 196. Next, IPA was removed from the resulting mixture using a rotary evaporator while heating to 55°C until the solid content of the mixture was around 30% by mass. Then, Viscoat™ 196 was added to this mixture so that the concentration of silica nanoparticles was 28.80% by mass, to prepare Sol 3.

[0136] Preparation of Radiation-Curable Ink Radiation-curable inks were prepared by the following method using the materials listed in Table 2. All blend amounts in Table 2 are in parts by mass.

[0137] (UV ink-C1) 2.500g of CN991NS, 6.500g of Viscoat™ 196, and 1.000g of NOAA were mixed in a glass bottle. 1.000g of Omnirad™ 184 as a photoinitiator and 0.010g of TEGO™ Rad 2250 as a polyether modified polymer were added to the mixture to prepare UV ink-C1.

[0138] (UV ink-C2) 2.073 g of Sol 1, 2.350 g of CN991NS, 4.656 g of Viscoat™ 196, and 0.940 g of NOAA were mixed in a glass bottle, and 1.000 g of Omnirad™ 184 was added as a photoinitiator to the mixture to prepare UV ink-C2.

[0139] (UV ink-C3) 2.500g of CN991NS, 5.500g of Viscoat™ 196, and 2.000g of MEDOL-10 were mixed in a glass bottle. 1.000g of Omnirad™ 184 as a photoinitiator, 0.100g of TEGO™ Flow 425 as a polyether modified polymer, and 0.100g of Genorad™ 22 were added to the mixture to prepare UV ink-C3.

[0140] (UV ink-E1~E13) Except for changing the composition ratios as shown in Table 2, UV inks E1 to E13 were prepared in the same manner as UV ink C2. [Table 2]

[0141] <Reference example> Cosmoshine™ A4100, a 50 micrometer thick PET base film, was used.

[0142] Comparative Example 1 Using a #20 Mayer rod, UV-C1 radiation curable ink was applied to the primer-treated side of Cosmoshine™ A4100, a 50 micrometer thick base film, to form a coating layer approximately 10 micrometers thick. The base film with the coating layer applied was passed through an ultraviolet irradiator (H-bulb (DRS model) from Fusion UV System Inc.) twice in an atmospheric (air) atmosphere to cure the coating layer. At this time, the illuminance was 700 mW / cm. 2 , cumulative light intensity 900mJ / cm 2 The coating layer was irradiated with ultraviolet rays (UV-A) under the conditions of: In this manner, a laminate of Comparative Example 1 having a coating layer with a thickness of about 10 micrometers was produced.

[0143] Comparative Example 2, Examples 1 to 13 Laminates of Comparative Example 2 and Examples 1 to 13 were each produced in the same manner as in Comparative Example 1, except that the radiation curable ink was changed from UV-C1 to each of the inks shown in Tables 3-1 to 3-3.

[0144] Example 14 Using an inkjet printer (inkjet head KM1024iLMHB, 720 x 720 dpi, manufactured by Konica Minolta, Inc.), an inkjet printing layer of about 10 micrometers in thickness was printed on the base film BK646420 while heating the radiation curable ink UV-E13 to 55°C. The base film to which the inkjet printing layer was applied was passed through an ultraviolet irradiator (H-bulb (DRS model) from Fusion UV System Inc.) twice in an atmospheric (air) atmosphere to cure the inkjet printing layer. At this time, the illuminance was 700 mW / cm 2 , cumulative light intensity 900mJ / cm 2 The inkjet printed layer was irradiated with ultraviolet rays (UV-A) under the following conditions: In this manner, a laminate of Example 14 having an inkjet printed layer with a thickness of about 10 micrometers was prepared.

[0145] Comparative Example 3 A laminate of Comparative Example 3 was produced in the same manner as in Example 14, except that the radiation curable ink was changed from UV-E13 to UV-C3.

[0146] The following evaluations were carried out for each sample of Reference Example, Examples 1 to 14, and Comparative Examples 1 and 2, and the results are shown in Tables 3-1 to 3-3. Here, the "SiO2 particle content" in the tables is based on the total weight (dry coating amount) of the coating layer or the inkjet printing layer. Scanning electron microscope photographs of the coating layers in the laminates of Comparative Examples 1 and 2 and Example 1 are shown in Figures 2 to 4, and scanning electron microscope photographs and optical photographs of the inkjet printing layers in the laminates of Example 14 and Comparative Example 3 are shown in Figure 5.

[0147] (Initial viscosity) The initial viscosity of the radiation curable ink at 55° C. was measured using a 20 mm cone-plate type parallel plate (manufactured by TA Instruments) at a rotation speed of 150 rpm using a Discovery HR-2 (DHR-2) rheometer (manufactured by TA Instruments).

[0148] (Appearance change after UV exposure) The appearance of the coating layer or the inkjet printing layer was visually observed before and after UV irradiation to determine whether it had changed. If the gloss appearance of the coating layer or the inkjet printing layer changed to a low gloss appearance after UV irradiation, it was judged as "yes", and if it did not change to a low gloss appearance, it was judged as "no".

[0149] (Surface gloss) In accordance with JIS Z8741, the surface gloss of each sample was measured at measurement angles of 20°, 60°, and 80° using a portable gloss meter BYK Gardner Micro-Tri-Gloss (BYK Japan Co., Ltd.).

[0150] (Adhesiveness) The adhesive performance between the substrate film and the coating layer or inkjet printing layer was evaluated by the cross-cut method according to JIS K 5600. A 5 x 5 grid with a grid spacing of 1 mm and Cellotape (trademark) CT-24 (manufactured by Nichiban Co., Ltd.) were used. When there was no peeling and / or chipping in the coating layer or inkjet printing layer, it was judged as "good", and when there was peeling and / or chipping, it was judged as "poor".

[0151] [Table 3] [Table 4] [Table 5]

[0152] It will be apparent to those skilled in the art that the above-described embodiments and examples can be modified in various ways without departing from the basic principles of the present invention, and that various improvements and modifications of the present invention can be made without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0153] 100 Laminate before irradiation 101 Base material 102 Surface layer before radiation exposure 103 Inorganic Nanoparticles 104 Binder resin 105 Surface layer after irradiation 110 Laminate after irradiation Some of the embodiments of the present disclosure are described in [Item 1] to [Item 16] below. [Item 1] A substrate, and Surface layer containing cured product of radiation curable ink A laminate comprising: the radiation curable ink contains inorganic nanoparticles, a polyether modified polymer, and at least one selected from a radiation curable polymerizable oligomer and a radiation curable polymerizable monomer; and The surface layer exhibits a 60 degree surface gloss of 50.0 GU or less. [Item 2] Item 2. The laminate according to item 1, wherein the radiation curable ink further comprises a compound of formula 1: R 1 -R 2 -Si(OR 3 ) 3 …Formula 1 In the formula, R 1 is an acryloyl group or a methacryloyl group, R 2 is an alkylene group having 5 to 12 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms. [Item 3] 3. The laminate according to item 2, wherein the compound of formula 1 is 8-(meth)acryloxyoctyltrimethoxysilane. [Item 4] 4. The laminate according to any one of items 1 to 3, wherein the radiation curable ink further comprises a non-functional silane coupling agent. [Item 5] 5. The laminate according to any one of items 1 to 4, wherein the radiation curable ink contains a difunctional urethane (meth)acrylate oligomer which is a radiation curable polymerizable oligomer. [Item 6] 6. The laminate according to any one of items 2 to 5, wherein the amount of each of the compound of formula 1 and the non-functional silane coupling agent, if present, is in the range of 0.030 to 0.090 mmol per 1 g of the inorganic nanoparticles. [Item 7] 7. The laminate according to any one of items 1 to 6, wherein the inorganic nanoparticles are contained in an amount of 2 to 20 mass % based on the total weight of the surface layer. [Item 8] 8. The laminate according to any one of items 1 to 7, wherein the inorganic nanoparticles have an average particle size of 5 nm or more and 150 nm or less. [Item 9] 9. The laminate according to any one of items 1 to 8, which is used for decorative purposes. [Item 10] A radiation-curable ink comprising inorganic nanoparticles, a polyether-modified polymer, and at least one member selected from a radiation-curable polymerizable oligomer and a radiation-curable polymerizable monomer. [Item 11] 11. The ink according to item 10, further comprising a compound of the following formula 1 and having an initial viscosity at 55° C. of 35.0 mPa s or less: R 1 -R 2 -Si(OR 3 ) 3 …Formula 1 In the formula, R 1 is an acryloyl group or a methacryloyl group, R 2 is an alkylene group having 5 to 12 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms. [Item 12] 12. The ink according to item 11, wherein the compound of formula 1 is 8-(meth)acryloxyoctyltrimethoxysilane. [Item 13] 13. The ink according to any one of items 10 to 12, further comprising a non-functional silane coupling agent. [Item 14] 14. The ink according to any one of items 10 to 13, comprising a difunctional urethane (meth)acrylate oligomer of a radiation-curable polymerizable oligomer. [Item 15] 15. The ink according to any one of items 11 to 14, wherein the amount of each of the compound of formula 1 and the non-functional silane coupling agent, if present, is in the range of 0.030 to 0.090 mmol per 1 g of the inorganic nanoparticles. [Item 16] 16. The ink according to any one of items 10 to 15, wherein the solvent content is 5% by mass or less.

Claims

1. A substrate, and Surface layer containing cured product of radiation curable ink A laminate comprising: the radiation curable ink comprises inorganic nanoparticles, a polyether modified polymer, a compound represented by the following formula 1, and at least one selected from a radiation curable polymerizable oligomer and a radiation curable polymerizable monomer, A laminate, wherein the surface layer contains aggregates of the inorganic nanoparticles and exhibits a 60 degree surface gloss of 50.0 GU or less. R 1 -R 2 -Si(OR 3 ) 3 ... Formula 1 In the formula, R 1 is an acryloyl group or a methacryloyl group, R 2 is an alkylene group having 5 to 12 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms.

2. 2. The laminate of claim 1, wherein the compound of formula 1 is 8-(meth)acryloxyoctyltrimethoxysilane.

3. The laminate according to claim 1 or 2, wherein the radiation curable ink further comprises a non-functional silane coupling agent.

4. 4. The laminate according to claim 1, wherein the radiation curable ink contains a difunctional urethane (meth)acrylate oligomer which is a radiation curable polymerizable oligomer.

5. The laminate according to any one of claims 1 to 4, wherein the amount of the compound of formula 1 and, if present, the non-functional silane coupling agent is in the range of 0.030 to 0.090 mmol per gram of the inorganic nanoparticles.

6. The laminate according to any one of claims 1 to 5, wherein the inorganic nanoparticles are contained in an amount of 2 to 20 mass % based on the total weight of the surface layer.

7. The laminate according to any one of claims 1 to 6, wherein the inorganic nanoparticles have an average particle size of 5 nm or more and 150 nm or less.

8. The laminate according to any one of claims 1 to 7, which is used for decorative purposes.

9. A radiation-curable ink for a surface layer comprising inorganic nanoparticles, a polyether-modified polymer, a compound of the following formula 1, and at least one selected from a radiation-curable polymerizable oligomer and a radiation-curable polymerizable monomer, the radiation-curable ink comprising an aggregate of the inorganic nanoparticles and exhibiting a 60 degree surface gloss of 50.0 GU or less: R 1 -R 2 -Si(OR 3 ) 3 ... Formula 1 In the formula, R 1 is an acryloyl group or a methacryloyl group, R 2 is an alkylene group having 5 to 12 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms, The amount of each of the compound of formula 1 and the non-functional silane coupling agent, if present, ranges from 0.030 to 0.090 mmol per gram of the inorganic nanoparticles.

Citation Information

Patent Citations

  • Energy ray-curable inkjet ink composition

    JP2009299057A

  • Embossed decorative sheet

    JP2011255552A

  • Curable composition and cured material thereof

    JP2013241515A

  • Window film, and method for producing window film

    JP2016165824A

  • Photocurable coating composition and use thereof

    JP2016525158A